1998
DOI: 10.1093/intimm/10.12.1891
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the gene loci that predispose to rheumatoid arthritis.

Abstract: We have searched the human genome for genes that predispose to rheumatoid arthritis (RA) using fluorescence-based microsatellite marker analysis and affected sib-pair linkage study. A panel of 41 Japanese families, each with at least two affected siblings, was typed for genome-wide 358 polymorphic microsatellite marker loci. Markers were amplified by the PCR using fluorescence-tagged primers and sized based on the difference of CA repeats on DNA. Linkage analysis was made using maximum lod score (MLS). The MLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
3
5

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 8 publications
9
128
3
5
Order By: Relevance
“…Other non-MHC candidate regions including the IDDM9 region of chromosome 3 and the proximal region of human chromosome 1 suggested in other preliminary studies, 23,25 were not confirmed in the current study. Similarly, these studies did not find a significant linkage for candidate loci suggested in the current study.…”
Section: Evidence For Independent Effect Of Tnf-ccontrasting
confidence: 92%
See 2 more Smart Citations
“…Other non-MHC candidate regions including the IDDM9 region of chromosome 3 and the proximal region of human chromosome 1 suggested in other preliminary studies, 23,25 were not confirmed in the current study. Similarly, these studies did not find a significant linkage for candidate loci suggested in the current study.…”
Section: Evidence For Independent Effect Of Tnf-ccontrasting
confidence: 92%
“…Similarly, these studies did not find a significant linkage for candidate loci suggested in the current study. Another putative susceptibility locus at Xq27 recently suggested 25 was not examined in the current study. Of additional note, another report 33 has provided some support for our initial studies suggesting linkage with CYP19 at 15q15.…”
Section: Evidence For Independent Effect Of Tnf-cmentioning
confidence: 78%
See 1 more Smart Citation
“…Chromosome region 1q31 has been implicated in linkage studies in lupus and multiple sclerosis (22)(23)(24). Multiple investigations have suggested linkage for chromosome region 1p36 in lupus (24)(25)(26), celiac disease (27), inflammatory bowel disease (28), and RA (29,30). This region was delineated further in adult RA using a case-control association design of single-nucleotide polymorphisms, resulting in a functional haplotype associated with RA that includes the gene PADI4 (31).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 We previously assigned three principal chromosome regions of linkage, D1S253/214, D8S556 and DXS1232, with maximum lod scores (MLSs) 3.77/6.13, 4.20/1.14 and 2.35/3.03, respectively, by single/multi-point analyses. 5 The death receptor 3 (DR3) gene was mapped in the vicinity of D1S214/ 253 by the GeneBridge 4.0 radiation hybrid panel. Based on the EBI/Sanger Institute ENSEMBL database, D1S214 and D1S253 reside at 6.7 and 6.0 Mb, respectively, and DR3 at 6.2 Mb of chromosome 1p36.…”
Section: Introductionmentioning
confidence: 99%